Impact of dynamic strategic capabilities on strategic entrepreneurship in presence of outsourcing of five stars hotels in Jordan - Sulieman Ibraheem Shelash Al-Hawary; Mohammad Sultan Al-Syasneh (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This research aims to investigate whether outsourcing mediates the impact of dynamic strategic capabilities on strategic entrepreneurship. The population of the research consists of top managers in five stars hotels. A sample of 215 respondents were selected for the research in which 186 questionnaires were valid for statistical analysis. Structural equation modelling (SEM) was used to test the hypotheses of the research. The results of the research indicate that outsourcing does not mediate the relationship between dynamic strategic capabilities and strategic entrepreneurship. All the dimensions of dynamic strategic capabilities have a statistical impact on strategic entrepreneurship, while the dynamic strategic capabilities dimension all affect outsourcing except the seizing capability. Based on the research results, managers and decision-makers have to focus on innovation functions by enhancing the role of knowledge management and R&D activities, as well as concentrate on employees training programs.
Keywords: M10; M19; 650; dynamic strategic capability; strategic entrepreneurship; outsourcing; five stars hotels; Jordan